“Am I Doing What I think I’m Doing?”: The Importance of a Theoretical Frame when Integrating Tablets in Teacher Education - Miller, Libbi; Nelson, Frederick Peinado; Yun, Cathy; Bennett, Lisa; Lopez Phillips, Emy (Educational (Re)naissance, 2020)
<span data-lucid-type="application/vnd.lucid.text" data-lucid-content=""t":"In the following self-study, we share our investigation of the shifts in faculty pedagogical beliefs, instructional practices, and curricular decision-making while engaged in a cycle of reflection on tablet-focused teacher education course. We conducted this inquiry into our practice, using Technological Pedagogical Content Knowledge (TPCK) and the Substitution-Augmentation-Modification-Redefinition (SAMR) model as frameworks to examine data from interviews and reflective writing. We conclude the need for the explicit connection of technology professional development, specifically tablet technology, with a meaningful theoretical framework, in order for faculty to engage in effective integration. We also share our model for examining the development of instructor’s thinking about integrating technology, including influences on thinking and classification of instructional decisions into the SAMR taxonomy. ","m":["s":0,"n":"c","v":"#000000ff","e":917,"s":0,"n":"fc","v":"Regular","e":917]">In the following self-study, we share our investigation of the shifts in faculty pedagogical beliefs, instructional practices, and curricular decision-making while engaged in a cycle of reflection on tablet-focused teacher education course. We conducted this inquiry into our practice, using Technological Pedagogical Content Knowledge (TPCK) and the Substitution-Augmentation-Modification-Redefinition (SAMR) model as frameworks to examine data from interviews and reflective writing. We conclude the need for the explicit connection of technology professional development, specifically tablet technology, with a meaningful theoretical framework, in order for faculty to engage in effective integration. We also share our model for examining the development of instructor’s thinking about integrating technology, including influences on thinking and classification of instructional decisions into the SAMR taxonomy.